STUDY OF THE PREVALENCE OF USE AND THE IMPACT OF HEADPHONES ON THE HEALTH STATUS OF STUDENTS - Niyazova O. A.; Khamidjanova M.T. (Modern American Journals, 2025)
In connection with the development of scientific and technological progress, an important part lives at a given time are different electronic devices [2-5]. Today mobile phones and MP3 players almost everyone has with headphones. They have become a familiar attribute of everyday life, ranging from schoolchildren listening to music in between lessons to people wanting to take time on public transport on their way to school or work. The auditory system — is one of the most important remote sensory systems of a person, which frolicked due to the occurrence of speech as a means of interpersonal communication. And despite the fact that the human auditory system is a unique and perfect mechanism, its capabilities are limited. Among adolescents and young adults aged 12-35 years, nearly 50% are exposed to unsafe volume sound from personal audio devices and are at risk of hearing loss, according to WHO research [10]. In 2004, more than 275 million people worldwide had moderate or severe hearing impairment, and by 2020, more than 30% of the world's population had hearing impairment. The leading position is occupied by damage to the sound-receiving apparatus due to the use of headphones [1, 10-11]. The problem of hearing impairment in young people with increasing technological progress and increased the availability of devices that allow you to listen to music through headphones is becoming increasingly common relevant and discussed in Uzbekistan and the world [6-10].